Stocks, origin, and future trajectories of hidden soil organic carbon in paleosols of blockfields in the high alpine permafrost region - A. Udke; M. E. D'Amico; M. Freppaz; E. Pintaldi; L. Minich; F. Hagedorn (2024)
Permafrost is warming because of global temperature increase, which alters the carbon cycle in these environments. While research has primarily focused on arctic permafrost, we are lacking data on the timing and magnitude of potential C accumulation and release in the alpine permafrost zone. These environments contain blockfields on mountain tops (>2900 m) with and without patterned ground, which are mainly vegetation free and therefore thought to be free of soil organic carbon (SOC). Motivated by the fact that coarse and fine material separates with freezing and thawing, we aimed to test whether alpine blockfields without vegetation are indeed SOC-free or whether they contain hidden carbon which might represent a CO2 source upon climatic warming. By sampling vegetated soils at the same or slightly lower elevation, we wanted to test how SOC stocks in blockfields will develop under climate warming in the near future. On four mountain tops (2900 to 3200 m a.s.l.) in the periglacial zone of the Eastern Swiss and NorthWestern Italian Alps, we removed up to onemeter-deep thick stone layer and excavated eleven soil profiles. While one location was completely vegetation free, the three other locations were influenced by active patterned ground with non-vegetated and sparsely vegetated patches within the same blockfield. At each site, we found dark and fine material beneath a stone cover of a few decimetres up to a meter. Preliminary results of the vegetation free location show a hidden SOC stock of 0.8 to 1.1 kgC·m-2 and narrow CN ratios of 9.0 to 10.1. Bulk soil 14C dating revealed an age of 4,000 to 12,900 years right beneath the stone cover (0-20 cm) and at greater depth (>80 cm) respectively. In agreement with our finding, Pintaldi et al. (2021) observed “hidden” SOC stock beneath active patterned ground on a mountain top plateau in North-West Italy. There are two possible origins of the hidden carbon: 1) soot deposition by natural and anthropogenic processes throughout the Holocene and 2) carbon accumulation ...